The Effect of Organizational Culture on the Quality of Accounting Information Systems - Nurliyani Nurliyani; Jufri Darma; Arfan Ikhsan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The purpose of this study is attempt to explain, empirically test, organizational culture on the quality of accounting information systems in the Regional Organization of Medan City. The survey was conducted on 38 respondents, namely the head of finance in the agency and department. Data were collected using a questionnaire. Basic SEM variance is used for data analysis. The results showed that organizational culture had a significant effect on the quality of accounting information systems. The results can be interpreted that organizational culture has an important role to realize the quality of accounting information systems.